The nail knot - Galligan, John (Galligan, John. Fly fishing mystery., 2022)
Rolling into little Black Earth, Wisconsin, intending to go fly fishing, Ned "Dog" Oglivie instead stumbles upon the body of a man trying to save Black Earth Creek, and wonders if by caring about the death of a stranger, he can recover his own life.